2010
DOI: 10.1088/0169-5983/42/1/015004
|View full text |Cite
|
Sign up to set email alerts
|

Application of porous material to reduce aerodynamic sound from bluff bodies

Abstract: Aerodynamic sound derived from bluff bodies can be considerably reduced by flow control. In this paper, the authors propose a new method in which porous material covers a body surface as one of the flow control methods. From wind tunnel tests on flows around a bare cylinder and a cylinder with porous material, it has been clarified that the application of porous materials is effective in reducing aerodynamic sound. Correlation between aerodynamic sound and aerodynamic force fluctuation, and a surface pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
75
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 129 publications
(101 citation statements)
references
References 7 publications
(9 reference statements)
25
75
1
Order By: Relevance
“…For this pitch ratio, the size of the formation region exceeds that for a uniform cylinder of fin diameter ( = c D T D / / ), whose formation region is approximately twice the size of that for ≥ c D / 0.361. A similar enlargement of the vortex formation region has been reported in previous studies of finned cylinders with low pitch ratios (Hamakawa et al, 2010;Khashehchi et al, 2014;Ryu et al, 2003) and porous cylinders (Naito and Fukagata, 2012;Sueki et al, 2010).…”
Section: Fig 4a-d and F Presents Representative Instantaneous Snapshsupporting
confidence: 88%
“…For this pitch ratio, the size of the formation region exceeds that for a uniform cylinder of fin diameter ( = c D T D / / ), whose formation region is approximately twice the size of that for ≥ c D / 0.361. A similar enlargement of the vortex formation region has been reported in previous studies of finned cylinders with low pitch ratios (Hamakawa et al, 2010;Khashehchi et al, 2014;Ryu et al, 2003) and porous cylinders (Naito and Fukagata, 2012;Sueki et al, 2010).…”
Section: Fig 4a-d and F Presents Representative Instantaneous Snapshsupporting
confidence: 88%
“…Results will be presented for various coating thickness (h=R ¼ 0:2, 0.3 and 0.4) and porosities (ϕ ¼0.8 and 0.95). Earlier studies on the application of porous materials for isolated bluff bodies have shown that effective flow stabilization can be achieved using high porosity (ϕ Z0:8) materials, with normalized permeability (Darcy number Da ¼ K=D 2 ) ranging from 10 À 1 to 10 À 3 [27,30,32,47].…”
Section: Resultsmentioning
confidence: 99%
“…We assumed that the closed-cell type would not be effective because flow is not able to enter the porous material. Verification of this supposition and the mechanism of noise reduction are described in the references [6]. Figure 1 metal) have an identical form referred to as a three-dimensional frame (net-like) structure.…”
mentioning
confidence: 89%